The Effects of the Goal-Based Approach on the Teaching of Yoruba as a Foreign Language: Yoruba Language Centre, University of Ibadan, as a Case Study (2017)
This paper focuses on the teaching of Yoruba as a foreign language at the Yoruba language Centre, University of Ibadan, Nigeria. It is a data-based study which attempts to examine the overall effects of the Goal-Based Approach on learning Yoruba as a foreign language. The paper adopts methodological triangulation research approach. Questionnaires were administered on Seven US based students who have come to be enmeshed in the Yoruba language and culture. The results were confirmed with personal interview and critical study of some of their write-ups. It was found that incorporating students’ goals, interests, and aspirations into the language learning curriculum tends to put more load on students, but that serves as a motivator in the language-learning process.